Response of Foliar Nutrient Management on Yield, Nutrient Uptake and Use Efficiency of Utera Rapeseed-Mustard Varieties Grown in Rice–Fallows of Lower Indo-Gangetic Plains - Saha, Somnath; Barik, Arun Kumar; Patre, Siddharth Sankar (International Journal of Bio-resource and Stress Management, 2025)
A two-year field experiment during winter seasons (November to February) of 2020–2021 and 2021–2022 was conducted to evaluate the effect of foliar spray of macro and micro nutrients on different rapeseed-mustard varieties under relay cropping in rice fallows. The results revealed that foliar spray of macro and micro nutrients had significant effect on seed yield, oil content, oil yield, nutrient uptake and use efficiency irrespective of rapeseed mustard varieties. Variety Binoy (B-9) registered significantly higher oil content (38.1%) over other two varieties but PM 28 showed its superiority when total oil yield per unit area was considered. Mustard variety PM 28 exhibited significantly higher total nitrogen (48.78 kg ha-1), phosphorus (11.79 kg ha-1), potassium (45.97 kg ha-1) and sulphur (23.29 kg ha-1) uptake both in seeds as well as in stover. Combined application of macro and micro nutrients i.e., spraying of N:P:K (19:19:19) @ 2% twice at 30 DAS and 45 DAS+ZnSO4 @ 0.05% at 40 DAS+Boron (20%) @ 0.1% at 50 DAS exhibited significantly higher seed yield, oil content, protein content, nutrient uptake of N, P, K, S, Zn and nitrogen use efficiency than other foliar spray of nutrients. Rapeseed-mustard variety PM-28 along with foliar application of N:P:K (19:19:19) @ 2% twice at 30 DAS and 45 DAS+ZnSO4 @ 0.05% at 40 DAS+Boron (20%) @ 0.1% at 50 DAS performed best in rice fallow of lower Indo-Gangetic plains.